2016
DOI: 10.1007/s00424-016-1861-2
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels in the Cx43 gap junction perinexus modulate ephaptic coupling: an experimental and modeling study

Abstract: Background It was recently demonstrated that cardiac sodium channels (Nav1.5) localized at the perinexus, an intercalated disc nanodomain associated with gap junctions (GJ), may contribute to electrical coupling between cardiac myocytes via an ephaptic mechanism. Impairment of ephaptic coupling by acute interstitial edema (AIE)-induced swelling of the perinexus was associated with arrhythmogenic, anisotropic conduction slowing. Given that Kir2.1 has also recently been reported to localize at intercalated discs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 34 publications
10
62
0
Order By: Relevance
“…Similar results were also obtained by Shaw and Rudy (1997, Figures 4, 6) and Veeraraghavan et al (2016, Figure 7) using different non-linear ionic models and our results are qualitatively consistent with these earlier studies. While Veeraraghavan et al (2016) also showed that a potassium conductance had a qualitatively similar effect on transverse conduction velocity to that seen here, this conductance had biphasic effect on longitudinal conduction velocity; however, their potassium channel was of the delayed rectifier type and may explain the differences between their results and those in this paper.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar results were also obtained by Shaw and Rudy (1997, Figures 4, 6) and Veeraraghavan et al (2016, Figure 7) using different non-linear ionic models and our results are qualitatively consistent with these earlier studies. While Veeraraghavan et al (2016) also showed that a potassium conductance had a qualitatively similar effect on transverse conduction velocity to that seen here, this conductance had biphasic effect on longitudinal conduction velocity; however, their potassium channel was of the delayed rectifier type and may explain the differences between their results and those in this paper.…”
Section: Discussionsupporting
confidence: 93%
“…However, their explanation was that Kir2.1 upregulation hyperpolarizes the cell resting membrane potential, thereby increasing sodium channel availability. Figure 2F shows that increasing G K1 alone actually decreases conduction velocity and this is in agreement with the experimental results of (Veeraraghavan and Poelzing, 2008) and Veeraraghavan et al (2016) and with data on reduction of conduction velocity by pinacidil activation of I K−ATP . With the discovery of reciprocal modulation (Milstein et al, 2012), we can see that I K1 upregulation induces a parallel upregulation of I Na which is the root cause of the increase in conduction velocity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Cx45 is upregulated in failing human hearts and is thought to be responsible for cell-to-cell coupling in Cx43-null ventricular myocytes [1214]. Of note, recent evidence suggest ephaptic mechanisms might also account for residual conduction in Cx43 knockout mice [15, 16]. The resulting altered coupling and slowed conductance enhances susceptibility to ventricular tachy-arrhythmias [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, we have used transmission electron microscopy (TEM) and gSTED super-resolution imaging that the perinexus, an intercalated disk (ID) nanodomain surrounding connexin43 (Cx43) gap junctions (GJ), possesses both characteristics. [4,5] Further, experimental disruption of close apposition between perinexal membranes slowed conduction and precipitated arrhythmias. Therefore, we investigated the localization and functions of Na V 1.5 and Na V β1 (a sodium channel auxiliary subunit and cell adhesion molecule [6]) within different ID nanodomains.…”
mentioning
confidence: 99%